LINGUAL FORM OF CONVERSATION IMPLICATURE ON ENDORSEMENT CONTENTS BY BALINESE CELEBGRAM - Gede Suarjaya, Anak Agung; Istri Wanik Warmadewi, Anak Agung; Dian Susanthi, I Gusti Ayu Agung; Angga Putra, I Made Agus (Center of Language and Cultural Studies [CLCS], 2022)
The main purpose of this research is to identify and describe the form of lingual implicature used in the endorsement content of Balinese celebgram. A qualitative approach was applied to this research. The endorsement video with Balinese language on @gek_ Cantik25 account is used as a data source. The data in this research is the utterances of the celebgram in lingual form which contains implicatures in the endorsement video in Balinese language. The data was collected by transcribing the video, then sorting the data according to the purpose of this research for further analysis. The data are presented with explanations that support the classification. There are three (3) lingual forms that contain implicatures in this research, namely declarative lingual forms, imperative lingual forms, and interrogative lingual forms. Meanwhile, the type of implicature contained does not depend on the lingual form but on the intent the speaker wants to convey.